Acute kidney injury after trauma: Prevalence, clinical characteristics and RIFLE classification - de Abreu, Krasnalhia Lívia S. (Medknow Publications, 2010)
BACKGROUND: Acute kidney injury (AKI) is an uncommon but serious complication after trauma. The objective of this study was to evaluate the prevalence, clinical characteristics and outcome of AKI after trauma. PATIENTS AND METHODS: This was a retrospective study performed from January 2006 to January 2008 in an emergency specialized hospital in Fortaleza city, northeast of Brazil. All patients with AKI admitted in the study period were included. Prevalence of AKI, clinical characteristics and outcome were investigated. RESULTS: Of the 129 patients admitted to the intensive care unit (ICU), 52 had AKI. The mean age was 30.1 ± 19.2 years, and 79.8% were males. The main causes of AKI were sepsis in 27 cases (52%) and hypotension in 18 (34%). Oliguria was observed in 33 cases (63%). Dialysis was required for 19 patients (36.5%). Independent risk factors associated with AKI were abdominal trauma [odds ratio (OR) = 3.66, P = 0.027] and use of furosemide (OR = 4.10, P = 0.026). Patients were classified according to RIFLE criteria as Risk in 12 cases (23%), Injury in 13 (25%), Failure in 24 (46%), Loss in 1 (2%) and End-stage in 2 (4%). Overall in-hospital mortality was 95.3%. The main cause of death was sepsis (24%). Mortality was 100% among patients with AKI. CONCLUSIONS: AKI is a fatal complication after trauma, which presented with a high mortality in the studied population. A better comprehension of factors associated with death in trauma-associated AKI is important, and more effective measures of prevention and treatment of AKI in this population are urgently needed.